Nurse Staffing Levels and Patient-Reported Missed Nursing Care - Dabney, Beverly Waller; Kalisch, Beatrice J (Journal of nursing care quality, 2015)
A total of 729 inpatients were surveyed using the MISSCARE Survey-Patient. Missed timeliness, patient reports of the time it took for them to receive care from nursing staff, was negatively associated with total nursing staff hours of care per patient-day (r = -0.09, P = .015), registered nurse (RN) hours per patient-day (r = -0.14, P = .0002), and RN skill mix (r = -0.13, P = .0004). RN skill mix was also a predictor of missed timeliness (P = .01).